It Takes a Team-Enhancing Student-Athlete Health and Well-Being through an Interprofessional Approach - Rebecca Steins; Anthony P. Breitbach; Michael Ross; Erica Ciarlo; Elena Melillo; Olivia Brant (MDPI AG, 2024)
Student-athlete well-being is a key objective for individuals working with or for university athletic departments. This paper will describe how a university athletic department used a team approach to enhancing student-athlete health and well-being. The Interprofessional Education Collaborative (IPEC) Core Competencies of (1) Values and Ethics; (2) Roles and Responsibilities; (3) Communication; and (4) Teams and Teamwork provide a guiding framework for interprofessional collaboration. (IPC; Interprofessional Education Collaborative, 2023). However, significant barriers exist in implementing IPC in university athletic departments and little research exists on how to overcome these barriers in university athletic departments to enhance student-athlete wellness. To address this gap, this paper will first provide a review of the literature on athlete well-being, followed by an applied section that describes the experience of an interprofessional wellness team (IWT) consisting of a clinical sports psychology doctoral student, a licensed mental health professional, an athletic trainer, and a sports dietitian. A case vignette is used to demonstrate how IPEC core competencies are operationalized by the team to address athlete health and well-being through IPC. Recommendations on the further implementation of IPC centered around student-athlete well-being will be provided.